Incidence of renal artery stenosis and its hemodynamic significance in patients subjected to angiography for suspected coronary artery disease - Deepak Arun Khore; Sushilkumar Dharamraj Navsare (Asian Journal of Medical Sciences, 2022)
Background: Renal artery stenosis (RAS) may occur alone (isolated anatomical RAS) or in combination with hypertension (renovascular or essential hypertension), renal insufficiency (ischemic nephropathy), or both. Renal artery stenting can be performed safely with nearly uniform technical success without exposing them to significant incremental risk. Aims and Objectives: The objectives of the study are as follows: (A) To study the incidence of RAS in suspected coronary artery disease patients. (B) To study the hemodynamic significance of RAS in patients diagnosed having RAS. (C) Should patients undergoing coronary angiography be subjected to routine renal angiography during the procedure? Materials and Methods: We prospectively did renal angiography of consecutive 100 patients, who underwent coronary angiography for their suspected coronary artery disease. Data regarding risk factors were recorded for every patient. Results: Out of 12 patients with RAS, 10 had significant stenosis (>50%) out of which seven patients showed hemodynamically significant RAS on captopril renogram. These were the patients having stenosis of 70% or more on renal angiography. Three patients having RAS 50–70% on renal angiography were not having hemodynamically significant lesion on captopril renograms. Conclusion: Renal angiography should be performed in patients undergoing coronary angiography. Femoral artery should be the preferred access site for coronary angiography to approach renal arteries. The patients with RAS should undergo captopril renography to evaluate the hemodynamic significance of the stenosis.